EARLY IDENTIFICATION OF AUTISM SPECTRUM DISORDERS: CLINICAL UTILITY OF ADOS - 2 FOR EARLY INTERVENTION SERVICES - Marina CALAC; Sergiu TOMA (Moldova State University, 2018)
Early identification of developmental delays is a key-principle in early intervention services that assures the optimal and most required supporting procedure for children who are at risk of ASD. The Autism Diagnostic Observation Schedule, 2nd edition (ADOS-2) is a diagnostic instrument which forms part of the recommended standardized tool for the assessment of Autism Spectrum Disorder (ASD), however raw scores are affected by age, development and language level. The utility of the ADOS-2 as used internationally offers the opportunity to practitioners and families to start EI services with a specific focus on behavioural and occupational therapy to stimulate the early development of the child according to his/her specific needs. The present article describes the initial results obtained results on initial and repeated assessments using ADOS-2 for 30 children aged 12-36 months children with developmental disabilities and children who have been referred to Center of Early Intervention Voincel because of possible autism spectrum disorder. All children are from high risk for ASD by M-CHAT results. The results confirm the relevance of initial assessment to determine the level of severity of Autism after a repeated assessment. IDENTIFICAREA PRECOCE A TULBURĂRILOR DE SPECTRU AUTISM: UTILITATEA CLINICĂ A ADOS - 2 PENTRU SERVICIILE DE INTERVENȚIE RAPIDĂ Identificarea precoce a întârzierilor de dezvoltare este un principiu-cheie în serviciile de intervenție timpurie care asigură procedura optimă și cea mai necesară de sprijin pentru copiii expuși riscului de TSA (Tulburări din spectru autism). Programul de Observație pentru Diagnosticul Autismului, ediția a 2-a (ADOS-2) este un instrument de diagnostic care face parte din instrumentele standardizate și recomandate pentru evaluarea tulburărilor de spectru autism (TSA). Utilitatea ADOS-2, constă în faptul că oferă posibilitatea clinicienilor și familiilor de a începe prestarea serviciilor de intervenție timpurie cu un accent special pe terapia comportamentală și ocupațională pentru a stimula dezvoltarea timpurie a copilului în funcție de nevoile sale specifice. Prezentul articol descrie rezultatele inițiale obținute în urma evaluărilor inițiale și repetate cu ajutorul ADOS-2 pentru 30 de copii în vârstă de 12-36 de luni cu copii cu tulburări de dezvoltare și copii care au fost evaluați la Centrul de intervenție timpurie  Voinicel din cauza riscului pentru tulburări de spectru autism. Toți copiii sunt expuși riscului crescut de ASD prin rezultatele M-CHAT. Rezultatele confirmă relevanța evaluării inițiale pentru a determina nivelul de severitate a autismului după o evaluare repetată.